2016
DOI: 10.1186/s12919-016-0046-5
|View full text |Cite
|
Sign up to set email alerts
|

Identity-by-descent estimation with population- and pedigree-based imputation in admixed family data

Abstract: BackgroundIn the past few years, imputation approaches have been mainly used in population-based designs of genome-wide association studies, although both family- and population-based imputation methods have been proposed. With the recent surge of family-based designs, family-based imputation has become more important. Imputation methods for both designs are based on identity-by-descent (IBD) information. Apart from imputation, the use of IBD information is also common for several types of genetic analysis, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Bhatnagar et al [ 30 ] compared the performance of methods that can be used to detect evidence for biased transmission and in doing so, also identified an additional potential QC step that may be useful in pedigree samples, as shown by application to observed vs. imputed sequence data. The papers by Sippy et al [ 31 ] and Saad et al [ 32 ] address approaches for selecting a subset of subjects for sequencing when there are constraints on the number of subjects that can be sequenced in a family study. Finally, the papers by Saad et al [ 32 ] and Lent et al [ 33 ] compared and evaluated approaches for combining both pedigree-agnostic and pedigree-based methods to improve genotype imputation from subjects with WGS data into those without.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Bhatnagar et al [ 30 ] compared the performance of methods that can be used to detect evidence for biased transmission and in doing so, also identified an additional potential QC step that may be useful in pedigree samples, as shown by application to observed vs. imputed sequence data. The papers by Sippy et al [ 31 ] and Saad et al [ 32 ] address approaches for selecting a subset of subjects for sequencing when there are constraints on the number of subjects that can be sequenced in a family study. Finally, the papers by Saad et al [ 32 ] and Lent et al [ 33 ] compared and evaluated approaches for combining both pedigree-agnostic and pedigree-based methods to improve genotype imputation from subjects with WGS data into those without.…”
Section: Methodsmentioning
confidence: 99%
“…The papers by Sippy et al [ 31 ] and Saad et al [ 32 ] address approaches for selecting a subset of subjects for sequencing when there are constraints on the number of subjects that can be sequenced in a family study. Finally, the papers by Saad et al [ 32 ] and Lent et al [ 33 ] compared and evaluated approaches for combining both pedigree-agnostic and pedigree-based methods to improve genotype imputation from subjects with WGS data into those without. Here, we will use “pedigree-agnostic” for genotype imputation methods that were designed for use on unrelated samples, but can be applied to samples from pedigrees, although without using the pedigree information.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…GIGI can handle large pedigrees efficiently, whereas Merlin cannot, thus requiring pedigree splitting or trimming. In previous studies, the performance of GIGI was compared to several population-based imputation methods (Saad et al 2016), while the performance of Merlin was separately evaluated on trimmed pedigrees (Lent et al 2016). The two programs were not compared directly on large pedigrees, although other studies have shown that both GIGI and Merlin perform well for rare variant imputation but not as well for common variants Saad and Wijsman 2014b).…”
mentioning
confidence: 99%